Social Media and Self-Esteem on Voting Behavior among Youth Samples in Rivers State, Nigeria - Enyelunekpo R. Roberts; Hope Lucky Ikirika; Emmanuel E. Uye (Lembaga Kajian Demokrasi dan Pemberdayaan Masyarakat (LKD-PM), 2025)
Voting behavior provides the sources of information about the interaction between individuals, society and politics. Studies linking voting behavior with social media and self-esteem among youths in Rivers State are lacking. Therefore, this study examines social media and self-esteem as predictors of voting behavior among youths in Rivers State, Nigeria. Cross-sectional survey was used while multistage sampling techniques were used to select one Local Government Area (LGA) and four communities while convenience sampling technique was used to sample the participants. Data were collected from 280 youths using a validated scale and analyzed using multiple regression analysis and independent samples t-test. Two hypotheses were tested and accepted at p =.001 level of significance. The result revealed that social media and self-esteem jointly predicted voting behavior among study participants (R2 = .49.1, F (2, 277) = 135.448, p = 001). Furthermore, social media usage (β = -.163, p =.001) and self-esteem (β = .618, p =.001) independently predicted voting behavior among study participants. Finally, gender significantly influenced voting behavior [t(278) = 17.308, p =.001] such that male participants showed higher voting behavior (M = 43.510, SD = 6.840) compared to their female counterparts (M= 30.420,SD = 2.748). The novelty of this finding is its being the first empirical studies that implicated social media usage, self-esteem and gender as predictors of voting behavior among dynamic youths in Rivers State. The study recommended that social media platforms should put appropriate messages to encourage youths’ participation in political affairs in their state and Nigeria. Abstrak Perilaku memilih menyediakan sumber informasi tentang interaksi antara individu, masyarakat, dan politik. Studi yang menghubungkan perilaku memilih dengan media sosial dan harga diri di kalangan remaja di Negara Bagian Rivers masih kurang. Oleh karena itu, studi ini mengkaji media sosial dan harga diri sebagai prediktor perilaku memilih di kalangan remaja di Negara Bagian Rivers, Nigeria. Survei cross-sectional digunakan, sementara teknik pengambilan sampel multitahap digunakan untuk memilih satu Daerah Pemerintah Daerah (LGA) dan empat komunitas, sementara teknik pengambilan sampel praktis digunakan untuk mengambil sampel peserta. Data dikumpulkan dari 280 remaja menggunakan skala yang telah divalidasi dan dianalisis menggunakan analisis regresi berganda dan uji-t sampel independen. Dua hipotesis diuji dan diterima pada tingkat signifikansi p = 0,001. Hasilnya mengungkapkan bahwa media sosial dan harga diri secara bersama-sama memprediksi perilaku memilih di antara peserta studi (R2 = .49.1, F (2, 277) = 135.448, p = 001). Lebih lanjut, penggunaan media sosial (β = -.163, p =.001) dan harga diri (β = .618, p =.001) secara independen memprediksi perilaku memilih di antara peserta studi. Akhirnya, gender secara signifikan memengaruhi perilaku memilih [t(278) = 17.308, p =.001] sehingga peserta laki-laki menunjukkan perilaku memilih yang lebih tinggi (M = 43.510, SD = 6.840) dibandingkan dengan rekan-rekan perempuan mereka (M = 30.420, SD = 2.748). Kebaruan dari temuan ini adalah menjadi studi empiris pertama yang mengimplikasikan penggunaan media sosial, harga diri dan gender sebagai prediktor perilaku memilih di antara pemuda yang dinamis di Rivers State. Studi ini merekomendasikan agar platform media sosial menyampaikan pesan yang tepat untuk mendorong partisipasi pemuda dalam urusan politik di negara bagian mereka dan Nigeria. Kata Kunci: media sosial; harga diri; perilaku memilih; negara bagian sungai